Autoimmune Pancreatitis Complicated by Spontaneous Subcapsular Splenic Haemorrhage - Hanna, Mina S; Terlevich, Ana; Przemioslo, Robert; Marden, Peter (JOP. Journal of the Pancreas, 2013)
Context Autoimmune pancreatitis is a rare but increasingly recognised condition with unique clinical, immunological and histological features. We report the first case of autoimmune pancreatitis associated with spontaneous splenic haemorrhage. Case report A 75-year-old man presented with severe epigastric pain radiating to the back associated with nausea and vomiting. A CT-scan of his abdomen showed a large pseudocyst within the pancreatic tail as well as a subcapsular splenic haemorrhage. His IgG4 levels were elevated and clinical history and investigations were consistent with severe acute pancreatitis, but were negative for other known causes of pancreatic disease. The patient was started on steroid therapy and improved dramatically clinically, immunologically and radiologically thus confirming the diagnosis of autoimmune pancreatitis. His splenic haemorrhage was managed conservatively in view of his haemodynamic stablity and eventually self-resolved. Conclusion Autoimmune pancreatitis should not be overlooked in cases of acute pancreatitis without other obvious etiology. Furthermore, superimposed splenic haemorrhage is a rare but important complication of autoimmune pancreatitis. Image: CT scan showing a large pseudocyst and subcapsular splenic haemorrhage.